New insights into the evolution of the Trypanosoma cruzi clade provided by a new trypanosome species tightly linked to Neotropical Pteronotus bats and related to an Australian lineage of trypanosomes. Issue 1 (December 2015) - Lima, Luciana; Espinosa-Álvarez, Oneida; Pinto, C.; Cavazzana Jr., Manzelio; Pavan, Ana; Carranza, Julio; Lim, Burton; Campaner, Marta; Takata, Carmen; Camargo, Erney; Hamilton, Patrick; Teixeira, Marta
Abstract Background Bat trypanosomes are implicated in the evolution of theT. cruzi clade, which harbours most African, European and American trypanosomes from bats and other trypanosomes from African, Australian and American terrestrial mammals, includingT. cruzi andT. rangeli, the agents of the American human trypanosomiasis. The diversity of bat trypanosomes globally is still poorly understood, and the common ancestor, geographical origin, and evolution of species within theT. cruzi clade remain largely unresolved. Methods Trypanosome sequences were obtained from cultured parasites and from museum archived liver/blood samples of bats captured from Guatemala (Central America) to the Brazilian Atlantic Coast. Phylogenies were inferred using Small Subunit (SSU) rRNA, glycosomal glyceraldehyde phosphate dehydrogenase (gGAPDH), and Spliced Leader (SL) RNA genes. Results Here, we describedTrypanosoma wauwau n. sp. fromPteronotus bats (Mormoopidae) placed in theT. cruzi clade, then supporting the bat-seeding hypothesis whereby the common ancestor of this clade likely was a bat trypanosome.T. wauwau was sister to the cladeT. spp-Neobats from phyllostomid bats forming an assemblage of trypanosome species exclusively of Noctilionoidea Neotropical bats, which was sister to an Australian clade of trypanosomes from indigenous marsupials and rodents, which possibly evolved from a bat trypanosome.T. wauwau was found in 26.5 % of thePteronotus bats examined, and phylogeographical analysis evidenced the wide geographical range of this species. To date, this species was not detected in other bats, including those that were sympatric or shared shelters withPteronotus. T. wauwau did not develop within mammalian cells, and was not infective to Balb/c mice or to triatomine vectors ofT. cruzi andT. rangeli . Conclusions Trypanosoma wauwau n. sp. was linked toPteronotus bats. The positioning of the cladeT. wauwau/T. spp-Neobats as the most basal Neotropical bat trypanosomes and closely related to an Australian lineage of trypanosomes provides additional evidence that theT. cruzi clade trypanosomes likely evolved from bats, and were dispersed in bats within and between continents from ancient to unexpectedly recent times.